Identification and analysis of candidate kinases for a function in gravitropic signalling using a novel phenotyping pipeline - Müller, Lukas K.B. (2019)
Roots use gravity to guide their growth (gravitropism). Gravitropism involves the establishment of an auxin gradient across the root, which is driven by polar auxin transport (PAT). Auxin acts as a growth inhibitor, triggering a differential growth response that results in root bending towards gravity.